14 de febrero de 1930: la transmisión de un acontecimiento y un mensaje / 14th February 1930: transmitting an event and a message - Francisca R. Quiroga (Studia et Documenta)
The article considers the way in which St. Josemaría Escrivá recalled and spoke to the faithful of Opus Dei about one of its foundational dates: 14th February 1930, when he understood that the message he had received on 2nd October 1928 was addressed not only to men but also to women. His transmission of 14th February 1930 contains some characteristics that remain the same and others that change over the years. The analysis is based on autobiographical testimonies, written and spoken, from St. Josemaría himself, in which he called to mind this date.